Phase change mortar as well as preparation and application thereof

By mixing the phase change working fluid with porous materials and mixing them with building materials in a specific proportion, the problem of mechanical strength of phase change materials in building materials is solved, and high-performance phase change mortar preparation is achieved, with excellent energy storage and mechanical strength.

CN119899012APending Publication Date: 2025-04-29DALIAN INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311409090.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-27
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

Existing phase change materials are difficult to mix organically with building materials in building materials, resulting in a decrease in mechanical strength or uneven thermal conductivity.

Method used

Porous materials such as clay, diatomaceous earth, and ceratops are mixed with phase-change working fluids such as paraffin, alkanes, and polyethylene glycol. By adjusting the proportion of materials such as cement, gypsum, fly ash and the addition of admixtures, high-performance organic mixing of phase-change materials and building materials is achieved.

Benefits of technology

The prepared phase change mortar has high energy storage capacity, excellent heat storage performance and good mechanical strength, and is suitable for building enclosures and thermal management equipment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0004517538610000011
    Figure HDA0004517538610000011
Patent Text Reader

Abstract

The preparation method specifically comprises the following process steps: preparing a novel phase-change energy-storage composite material, and directly mixing the novel phase-change energy-storage composite material with cement, gypsum, fly ash, coal gangue, lightweight aggregate, an additive and other materials. The phase-change temperature zone of the high-strength phase-change mortar is adjustable (20-50 DEG C), performance design can be carried out according to the use environment, and the use range of the high-strength phase-change mortar is expanded. The material is simple in preparation process, good in material stability and high in energy storage density and mechanical strength, and can be used for heat storage, heat management and the like of building enclosure walls.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention discloses a phase change mortar and a preparation method thereof, belongs to the field of building material science and technology, and particularly relates to an energy storage temperature control building material. Background Art

[0002] Phase change materials are a class of substances that can absorb or release large amounts of energy during a phase change process. One of the most common phase change materials is phase change energy storage materials, which can absorb heat and store it, and then release the stored energy when needed. These materials have a wide range of applications in the fields of energy conservation and environmental protection, such as solar energy storage systems and temperature control systems in smart buildings. Phase change materials can also be used in temperature sensors, medical equipment, food storage and transportation, and many other fields.

[0003] Phase change mortar is a special building material that can undergo phase change when the temperature changes, thus realizing intelligent temperature control of buildings. This mortar can absorb and store heat in hot seasons and release heat in cold seasons, thereby improving the energy efficiency and comfort of buildings. Phase change mortar has been widely used in the field of green buildings, helping to reduce energy consumption of buildings and alleviate the burden on the environment.

[0004] At present, phase change materials are mainly added by microcapsule technology and shaped phase change material packaging. Microcapsules still have disadvantages such as easy leakage in actual application, while shaped phase change materials are relatively simple to introduce support materials into the phase change material system, but there will be uneven heat conduction and loss of mechanical strength. Therefore, a preparation method that can organically mix phase change materials with building materials and retain strong mechanical strength is extremely important.

[0005] Overall, high-strength phase change mortar represents an important technology for the construction industry to move towards a smarter and more sustainable direction. It has the potential to reduce energy consumption in buildings, improve indoor comfort, and help address the challenges of climate change and energy efficiency. This background technology provides strong support for the development of the future construction field and is expected to become an innovative and important achievement in the field of building materials. Summary of the invention

[0006] The present invention adopts clay, diatomaceous earth, ceramsite to mix and absorb phase change media such as paraffin, alkane, polyethylene glycol, etc., and realizes high-performance organic mixing of phase change materials and building materials by adjusting and optimizing the ratio of cement, gypsum, fly ash, coal gangue powder, aggregate, admixture and water and the addition of admixture.

[0007] The synthetic phase change mortar includes the following steps:

[0008] (1) Mixing a certain proportion of phase change fluid and porous material to obtain a phase change material;

[0009] (2) The phase change material prepared in (1) is mixed with cement, gypsum, fly ash, coal gangue powder, aggregate, admixture and water in a certain proportion.

[0010] Furthermore, the phase change working fluid in step (1) is one or more of paraffin, alkane, polyethylene glycol, and its phase change temperature range is 15-50°C;

[0011] The porous material in step (1) includes but is not limited to clay, diatomaceous earth and ceramsite;

[0012] In the step (1), the porous materials such as pottery clay, diatomaceous earth and ceramsite are preferably treated, and the treatment methods of the porous materials include but are not limited to drying (50-100° C.), roasting (350-500° C., preferably 450° C.), acid washing (one or more of hydrochloric acid, acetic acid, and sulfuric acid, with a concentration range of 0.1-1M), alkali washing (one or more of sodium hydroxide and potassium hydroxide, with a concentration of 0.1-1M), water washing, etc.;

[0013] In step (1), the mass ratio of the phase change medium to the phase change material is in the range of 5% to 60%, preferably in the range of 10% to 50%;

[0014] The mixed material in step (2) comprises two or more of cement, gypsum, fly ash, coal gangue and aggregate;

[0015] The admixture in step (2) includes, but is not limited to, one or more of a water reducing agent, an early strength agent, a reinforcing agent, and glass fiber, and the specific amount used is in accordance with the product instructions;

[0016] Further, the mass ratio of phase change material, cement, gypsum, fly ash, coal gangue powder, aggregate, admixture and water is 1: (0.1-0.8, preferably 0.4-0.8): (0.1-0.4, preferably 0.2-0.4): (0-0.2, preferably 0-0.05): (0-0.2, preferably 0-0.05): (0-0.5, preferably standard sand 0.2-0.4): (0.0001-0.005, preferably 0.0001-0.002): (0.2-1, preferably 0.4-0.8);

[0017] Furthermore, the present invention can adjust the proportion of materials used according to different usage scenarios to achieve the requirements of temperature control performance and scene intensity;

[0018] Furthermore, the water reducer used complies with the standard: JGT223-2017 Polycarboxylic acid high performance water reducer; the gangue powder complies with the standard: GB / T 29163-2012 Technical Guidelines for Gangue Utilization; the reference standard for the addition of gangue powder, fly ash and aggregate: JBJ 55-2011 Ordinary Concrete Mix Design Code.

[0019] The phase change mortar prepared by the present invention has a high phase change material loading amount, excellent heat storage capacity and is easy to use. The system can be used as a functional substance for heat energy conversion and storage and heat energy management equipment.

[0020] The invention is convenient to use, and can be directly extruded and solidified into phase change bricks or phase change plates, or added with materials such as steel bars and mesh cloth for solidification to form blocks, etc., which is conducive to practical application production and on-site construction. It can also be used as a building enclosure structure and a building facing material.

[0021] The phase change temperature range of this high-strength phase change mortar is adjustable (20-50°C), and its performance can be designed according to the use environment, which expands its scope of use. The preparation process is simple, the material has good stability, high energy storage density and mechanical strength, and can be used for heat storage and thermal management of building enclosure walls. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 The test curve of the sample temperature control performance DETAILED DESCRIPTION

[0023] The following is a detailed description of an embodiment of the present invention. This embodiment is implemented on the premise of the technical solution of the present invention, and a detailed implementation method and a specific operation process are given, but the protection scope of the present invention is not limited to the following embodiment.

[0024] Example 1

[0025] (1) The porous material is clay, which is acid-washed with 0.1M acetic acid solution, calcined at 450℃ for 2h, and then mixed with n-octadecane at 50℃. The proportion of each component in the phase change mortar is: by mass ratio, n-octadecane: clay: P·O32.5 cement: gypsum: coal gangue powder (Longze Building Materials Co., Ltd., 200 mesh particle size): water reducer (polycarboxylic acid high-performance water reducer, Huaxuan High-tech Co., Ltd.): ionic soil solidifier (Oulian Hongda Industry and Trade Co., Ltd.): water = 0.24: 0.76: 0.80: 0.12: 0.08: 0.0024: 0.0001: 0.5, stirred to obtain phase change mortar; the phase change mortar after sufficient stirring was cured at a temperature of 20℃ and a humidity of 95±5% for 7d, and then naturally cured for 28d to obtain a phase change mortar sample. The sample is formed according to the requirements of standard JGJ / T 70-2009, and the side length of the sample is 70.7mm.

[0026] (2) The process and conditions are the same as above, except that no octadecane is added. A comparative sample is prepared according to the above method.

[0027] The temperature control performance of the sample and the comparison sample were tested. The sample and the comparison sample were heated from -14℃ to 45℃ respectively. The comparison sample continued to heat up to 45℃ and no constant temperature range was found. The phase change mortar sample had a more obvious constant temperature platform at 24-28℃, and the energy storage and thermal insulation effect was very significant. Test data can be found at Figure 1 The test curve of the sample's temperature control performance. The compressive test result is 10MPa, which meets the requirements for building maintenance structures.

[0028] Example 2

[0029] The porous material is clay, which is calcined at 450°C for 2h after alkaline washing with 1M NaOH aqueous solution, and then mixed at 50°C after adding paraffin. The distribution ratio of each component in the phase change mortar is: by mass ratio, paraffin: clay: P·O32.5 cement: gypsum: first-class fly ash: standard sand (China ISO standard sand, Xiamen Ace Standard Sand Co., Ltd.): water reducer (polycarboxylic acid high-performance water reducer, Huaxuan High-tech Co., Ltd.): ionic soil solidifier (Oulian Hongda Industry and Trade Co., Ltd.): water = 0.3: 0.7: 0.60: 0.2: 0.12: 0.3: 0.0024: 0.0002: 0.5, stirred to obtain phase change mortar; cured for 7d at a temperature of 20°C and a humidity of 95±5%, and then naturally cured for 28d to obtain a phase change mortar sample. The sample is formed according to the requirements of standard JGJ / T 70-2009. The side length of the sample is 70.7mm. The strength grade is 7.5MPa after testing, and the constant temperature range is 24-29℃.

[0030] Example 3

[0031] The porous material is 1-5mm ceramsite, which is washed with water and dried at 80℃ for 5 hours and then mixed with polyethylene glycol at 50℃. The distribution ratio of each component in the phase change mortar is: by mass ratio, polyethylene glycol (2000): ceramsite: P·O32.5 cement: gypsum: fine aggregate (fineness modulus 2.2-3.0): water reducer (polycarboxylic acid high-performance water reducer, Huaxuan High-tech Co., Ltd.): early strength agent (Hongxiang Building Admixture Factory): water = 0.2: 0.8: 0.6: 0.2: 0.12: 0.3: 0.0024: 0.001: 0.5, and the phase change mortar sample is cured for 7 days at a temperature of 20℃ and a humidity of 95±5%, and then naturally cured for 28 days. The sample was formed according to the requirements of standard JGJ / T 70-2009. The side length of the sample was 70.7 mm. The constant temperature range after testing was 38-42°C.

[0032] Example 4

[0033] The porous material is diatomite, which is dried at 60°C for 2 hours and then mixed with n-octadecane at 50°C. The distribution ratio of each component in the phase change mortar is: by mass ratio, n-octadecane: diatomite: P·O32.5 cement: gypsum: coal gangue powder (Longze Building Materials Co., Ltd., 350 mesh): standard sand (China ISO standard sand, Xiamen AIS Standard Sand Co., Ltd.): water reducer (polycarboxylic acid high-performance water reducer, Huaxuan High-tech Co., Ltd.): glass fiber (diameter about 12-20μm, length 6-10mm): water = 0.5: 0.5: 0.8: 0.2: 0.12: 0.3: 0.0024: 0.0001: 0.5, and the phase change mortar sample is cured for 7 days at a temperature of 20°C and a humidity of 95±5%, and then naturally cured for 28 days. The sample was formed according to the requirements of standard JGJ / T 70-2009. The side length of the sample was 70.7 mm. The constant temperature range after testing was 24-28°C.

[0034] Example 5

[0035] The porous material is diatomite, which is dried at 50°C for 12 hours and then mixed with n-octadecane at 50°C. The proportion of each component in the phase change mortar is as follows: by mass ratio, n-octadecane: diatomite: P·O32.5 cement: gypsum: coal gangue powder (Longze Building Materials Co., Ltd., 350 mesh): first-class fly ash: standard sand (China ISO standard sand, Xiamen AISOU Standard Sand Co., Ltd.): water reducer (polycarboxylic acid high-performance water reducer, Huaxuan High-tech Co., Ltd.): ionic soil stabilizer (Oulian Hongda Industry and Trade Co., Ltd.): water = 0.25: 0.75: 0.8: 0.2: 0.2: 0.2: 0.3: 0.0024: 0.0001: 0.8, and the phase change mortar sample was cured for 7 days at a temperature of 20°C and a humidity of 95±5%, and then naturally cured for 28 days. The sample is formed according to the requirements of standard JGJ / T 70-2009. The side length of the sample is 70.7mm. The compression test result is 7.5MPa, which meets the requirements for building maintenance structures. The constant temperature range is 24-28℃.

[0036] Example 6

[0037] The porous material is diatomite, which is dried at 50°C for 12 hours and then mixed with paraffin at 50°C. The proportion of each component in the phase change mortar is as follows: by mass ratio, paraffin: diatomite: P·O32.5 cement: gypsum: coal gangue powder (Longze Building Materials Co., Ltd., 350 mesh): first-class fly ash: standard sand (China ISO standard sand, Xiamen AIS Standard Sand Co., Ltd.): water reducer (polycarboxylic acid high-performance water reducer, Huaxuan High-tech Co., Ltd.): ionic soil solidifier (Oulian Hongda Industry and Trade Co., Ltd.): water = 0.4: 0.6: 0.1: 0.4: 0.2: 0.2: 0.001: 0.0001: 0.3, and the phase change mortar sample is cured for 7 days at a temperature of 20°C and a humidity of 95±5%, and then naturally cured for 28 days. The sample is formed according to the requirements of standard JGJ / T 70-2009. The side length of the sample is 70.7mm. The compression test result is 5.0MPa, which meets the requirements for building maintenance structures. The constant temperature range is 25-33℃.

[0038] Example 7

[0039] The porous material is diatomite, which is dried at 50°C for 12 hours and then mixed with paraffin at 50°C. The proportion of each component in the phase change mortar is: by mass ratio, paraffin: diatomite: P·O32.5 cement: gypsum: fine aggregate (fineness modulus 2.2-3.0): water reducer (polycarboxylic acid high-performance water reducer, Huaxuan High-tech Co., Ltd.): ionic soil solidifier (Oulian Hongda Industry and Trade Co., Ltd.): water = 0.4: 0.6: 0.4: 0.4: 0.5: 0.0024: 0.0001: 0.6, and the phase change mortar sample is obtained by curing for 7 days at a temperature of 20°C and a humidity of 95±5%, and then naturally curing for 28 days. According to the requirements of standard JGJ / T70-2009, the sample is formed into a cube with a side length of 70.7mm, and the compressive test result is 7.5MPa, which meets the requirements for building maintenance structures. The tested constant temperature range is 25-33℃.

[0040] Comparative Example 1

[0041] The patent discloses a method for preparing a compound fatty acid low-temperature phase change cement mortar and its preparation method (111484297A), which uses expanded graphite as a porous skeleton to adsorb phase change materials to form a composite phase change material, and then compounds the composite phase change material with cement, water and sand to form a phase change cement mortar.

[0042] Compared with what is mentioned in Example 1 of this patent, this patent application directly uses aggregates in cement mortar (such as expanded clay, diatomaceous earth, etc.) for treatment as carriers for loading phase change materials, thereby increasing the occupancy rate of phase change materials in the overall phase change mortar, increasing energy storage capacity, and thus enhancing temperature regulation performance.

[0043] Comparative Example 2

[0044] The preparation method of the phase change cement mortar mentioned in Example 1 of the patent "A method for preparing low-temperature phase change cement mortar with tetradecane expanded graphite" (111592303A) has the same principle as that of comparative example 1, that is, a skeleton structure that can absorb phase change material is introduced to prevent leakage of the phase change material.

[0045] Similarly, compared to the preparation method mentioned in Example 1 of this patent, this patent application does not introduce additional skeleton adsorption materials, but directly achieves the characteristics of adsorbing phase change materials by modifying the aggregate structure in cement, thereby improving the performance of the overall phase change cement mortar.

[0046] Comparative Example 3

[0047] The preparation method of diatomaceous earth mortar mentioned in the embodiment of the patent "An eco-friendly diatomaceous earth mortar for interior partition boards" (105948670A) uses the same raw materials as the patent, such as expanded clay, diatomaceous earth, cement, sand, water reducer, etc., but its compressive strength (5.5MPa) is not as good as the compressive strength of the material disclosed in the patent. At the same time, the patent does not use phase change materials and does not have the temperature adjustment function compared with the patent.

Claims

1. A phase change mortar, characterized in that: It includes phase change material, cement, gypsum and water, and may or may not contain one or more of fly ash, coal gangue, aggregate and admixture; The phase change material is composed of a phase change medium and a porous material, and the mass ratio of the phase change medium in the phase change material is in the range of 5-60% (preferably 10-50%); The mass ratio of phase change material, cement, gypsum, fly ash, coal gangue powder, aggregate, admixture and water is 1: (0.1-0.8, preferably 0.4-0.8): (0.1-0.4, preferably 0.2-0.4): (0-0.:2, preferably 0-0.05): (0-0.2, preferably 0-0.05): (0-0.5, preferably standard sand 0.2-0.4): (0.0001-0.005, preferably 0.0001-0.002): (0.2-1, preferably 0.4-0.8).

2. The phase change mortar according to claim 1, characterized in that: The phase change working fluid is one or more of paraffin, alkane, and polyethylene glycol, and its phase change temperature range is 15-50°C.

3. The phase change mortar according to claim 1, characterized in that: The porous material includes, but is not limited to, one or more of clay, diatomaceous earth and ceramsite (with a particle size greater than 1-5 mm, preferably greater than 1-3 mm).

4. The phase change mortar according to claim 1 or 3, characterized in that: The porous material is preferably pretreated before use. The pretreatment methods of the porous material include but are not limited to drying (50-100°C, time 1-16 hours), roasting (350-500°C, preferably 450-480°C, time 0.5-6 hours), acid washing (one or more of hydrochloric acid, acetic acid, and sulfuric acid, with a concentration range of 0.1-1M), alkali washing (one or more of sodium hydroxide and potassium hydroxide, 0.1-1M concentration), water washing, etc. One or more of the above.

5. The phase change mortar according to claim 1, characterized in that: The admixtures include but are not limited to one or more of a water reducing agent, an early strength agent, a reinforcing agent, and glass fiber.

6. The phase change mortar according to claim 1, characterized in that: The aggregates include but are not limited to one or two of fine aggregate (fineness modulus 2.2-3.0) and standard sand (GB / T17671). Head.

7. A method for preparing the phase change mortar according to any one of claims 1 to 6, characterized in that: The specific process steps are as follows: (1) mixing a phase change working fluid with a porous material and / or a treated porous material to obtain a phase change material; (2) Mixing the phase change material prepared in (1) with cement, gypsum, water, admixtures, and materials such as fly ash (or not), coal gangue powder (or not), and aggregate (or not) in a desired proportion.

8. Use of the phase change mortar according to any one of claims 1 to 6 as a building material.